Этапная аблация длительно персистирующей формы фибрилляции предсердий - Карпенко, Ю.И.; Горячий, А.В.; Найденко, Н.В.; Абрамова, А.А. (Таврический медико-биологический вестник, 2013)
У даному дослідженні представлено загальне розташування і ефект додаткових аплікацій ключових
зон комплексної фракціонованої активності після ізоляції легеневих вен у пацієнтів з довго персистуючою
формою фібриляції передсердь. Combinative wide antral circular PVI, in conjunction with ablation of CFA zones increases the efficiency of
treatment of AF and significantly reduces time of procedure and X-ray burden on staff and patient. Stand-alone
ablation of CFA zones is not effective enough and requires expansion of the procedure.